Comparative Analysis of Wind Energy Potential with Nakagami and Weibull Distribution Methods for Wind Turbine Planning - Suriadi Suriadi; Muna Nabilah; Muzakir Zainal; Muhammad Yanis; Marwan Marwan; Hafidh Hafidh; Muzailin Affan (Graduate Program of Syiah Kuala University, 2023)
Wind energy is renewable energy used as an energy source for wind power plants (PLTB). The most common distribution method used to model wind speed distribution data is the Weibull distribution. The Nakagami distribution has begun to be widely used in several studies to model wind speed distribution data. The Nakagami distribution is considered an alternative to the Weibull distribution in modeling wind speed distribution data. This study aims to compare the distribution of Nakagami and Weibull in analyzing wind power potential and calculating the resulting Wind Energy Production (WEP), using wind speed distribution data from both distributions in Kuta Raja, Banda Aceh and Lhoknga, Aceh Besar. The wind speed data used is satellite data (secondary data) downloaded via windguru.cz, with the most stable wind speed being a wind speed of 3-5 m/s. The value of wind power potential at the Kuta Raja location, Banda Aceh was obtained at 64.16% with the Nakagami distribution and 62.73% with the Weibull distribution, and 73.60% with the Nakagami distribution and 73.28% at the Lhoknga location, Aceh Besar. The comparison of these two distributions produces a Weibull distribution that is superior to the Nakagami distribution for both locations, where the Weibull distribution has a smaller error value and produces a WEP value that is in accordance with the actual/observable data compared to the Nakagami distribution. In this study, the Nakagami distribution has results that make this distribution an alternative or comparison to the Weibull distribution in distributing wind speed data with further research.